EV purchase intention: Environmental, infrastructure, and perceived value mediating attitude - Permana, Arya Rezky; Wisnalmawati (Department of Accounting, Faculty of Business, Universitas PGRI Yogyakarta, 2025)
The acceleration of electric vehicle (EV) adoption is critical for Indonesia’s green transition, yet consumer acceptance varies across regions. This study aimed to analyze the factors shaping EV purchase intention in D.I. Yogyakarta, with a focus on testing the mediating role of Attitude. Specifically, this research investigated the “attitude-behavior gap” in Environmental Concern and the “range anxiety” anomaly related to Charging Infrastructure. This study employed a quantitative approach with an explanatory research design, involving 125 respondents in DIY collected via purposive sampling. Primary data were analyzed using Partial Least Squares Structural Equation Modelling (PLS-SEM). The results indicated that the measurement and structural models were valid and reliable. Hypothesis testing revealed three main findings: (1) Environmental Concern had no direct effect on Purchase Intention, but had a significant effect through Attitude (complete mediation), confirming an attitude-behavior gap; (2) Charging Infrastructure surprisingly had a significant adverse effect on Purchase Intention, indicating that awareness of uneven SPKLU distribution in the DIY triggered range anxiety; and (3) Perceived Value was the strongest direct driver of Purchase Intention. The practical implication is that the government and PLN must prioritize the equitable distribution of SPKLU, while marketers should emphasize perceived value to accelerate EV adoption.